Water use of Juniperus virginiana trees encroached into mesic prairies in Oklahoma, USA - Caterina, Giulia L. [UNESP]; Will, Rodney E.; Turton, Donald J.; Wilson, Duncan S.; Zou, Chris B. (Wiley-Blackwell, 2014)
Juniperus virginiana (eastern redcedar) is encroaching into mesic prairies of the southern Great Plains, USA, and is altering the hydrologic cycle. We used the thermal dissipation technique to quantify daily water use of J. virginiana into a mesic prairie by measuring 19 trees of different sizes from different density stands located in north-central Oklahoma during 2011. We took the additional step to calibrate our measurements by comparing thermal dissipation technique estimates to volumetric water use for a subset of trees. Except for days with maximum air temperature below -3 degrees C, J. virginiana trees used water year round, reached a peak in late May, and exhibited reduced water use in summer when soil water availability was low. Overall daily average water use was 24 l (+/- 21.81 s.d.) per tree. Trees in low density stands used more water than trees with similar diameters from denser stands. However, there was no difference in water use between trees in different density stands when expressed on a canopy area basis. Approximately 50% of variation in water use that remained after accounting for the factors site, tree, and day was explained using a physiologically-based model that included daily potential evapotranspiration, maximum vapour pressure deficit, maximum temperature, solar radiation, and soil water storage between 0 and 10 cm. Our model suggested that a J. virginiana woodland with a closed canopy is capable of transpiring almost all precipitation reaching the soil in years with normal precipitation, indicating the potential for encroachment to reduce water yield for streamflow and groundwater recharge. Copyright (C) 2013 John Wiley & Sons, Ltd.
Keywords: eastern redcedar; transpiration; sap flux; Granier-type sensor; Great Plains